Integrating Physical Activity and Mental Well-Being in Youth Sports: A Contemporary Perspective in Football Training - Ahmad Firdaus Bin Rahman; Maria Lourdes Santos (Jambura Arena Sport, 2026)
Youth sports, particularly football, play a significant role in promoting both physical fitness and psychological well-being among young individuals. This study aims to examine the integration of physical activity and mental well-being within youth football training programs using a qualitative descriptive approach based on a review of peer-reviewed international journals published between 2021 and 2025. The findings indicate that structured football training not only improves physical attributes such as endurance, strength, and coordination but also enhances emotional regulation, self-confidence, and social interaction among youth athletes. In addition, the incorporation of psychological components, including goal setting, intrinsic motivation, and mindfulness practices, has been shown to increase athlete engagement while reducing stress, anxiety, and burnout. The study further emphasizes the importance of adopting athlete-centered coaching approaches that prioritize enjoyment, personal development, and mental resilience alongside performance outcomes. The integration of physical and psychological training is therefore essential in creating a balanced and sustainable sports environment for young athletes. In conclusion, embedding mental well-being into football training provides a comprehensive framework for developing healthier, more adaptive, and resilient youth athletes, offering important implications for coaches, educators, and policymakers in designing effective youth sports programs.